Flavonol-induced changes in PIN2 polarity and auxin transport in the Arabidopsis thaliana rol1-2 mutant require phosphatase activity - Kuhn, Benjamin M; Nodzyński, Tomasz; Errafi, Sanae; Bucher, Rahel; Gupta, Shibu; Aryal, Bibek; Dobrev, Petre; Bigler, Laurent; Geisler, Markus; Zažímalová, Eva; Friml, Jiří; Ringli, Christoph (Scientific reports, 2017)
The phytohormone auxin is a major determinant and regulatory component important for plant development. Auxin transport between cells is mediated by a complex system of transporters such as AUX1/LAX, PIN, and ABCB proteins, and their localization and activity is thought to be influenced by phosphatases and kinases. Flavonols have been shown to alter auxin transport activity and changes in flavonol accumulation in the Arabidopsis thaliana rol1-2 mutant cause defects in auxin transport and seedling development. A new mutation in ROOTS CURL IN NPA 1 (RCN1), encoding a regulatory subunit of the phosphatase PP2A, was found to suppress the growth defects of rol1-2 without changing the flavonol content. rol1-2 rcn1-3 double mutants show wild type-like auxin transport activity while levels of free auxin are not affected by rcn1-3. In the rol1-2 mutant, PIN2 shows a flavonol-induced basal-to-apical shift in polar localization which is reversed in the rol1-2 rcn1-3 to basal localization. In vivo analysis of PINOID action, a kinase known to influence PIN protein localization in a PP2A-antagonistic manner, revealed a negative impact of flavonols on PINOID activity. Together, these data suggest that flavonols affect auxin transport by modifying the antagonistic kinase/phosphatase equilibrium.
Keywords: proteiny huseníčku; Protein Phosphatase 2; Arabidopsis Proteins; proteinfosfatasa 2; kyseliny indoloctové; mutace; Flavonoids; Glucosyltransferases; Mutation; Indoleacetic Acids; flavonoidy; Arabidopsis; glukosyltransferasy